2015
DOI: 10.1007/s13213-015-1053-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antibiotic resistance, virulence and plasmid profiles of Vibrio parahaemolyticus from a tropical estuary and adjoining traditional prawn farm along the southwest coast of India

Abstract: Vibrio parahaemolyticus, autochthonous to estuarine, marine, and coastal environments throughout the world, is a leading cause of foodborne gastroenteritis in Asia as well as in other countries. Considering their role in disease outbreaks, water and sediment samples from two different environments along the southwest coast of India, such as the Cochin estuary, which is a tourist hot spot and a traditional prawn farm, were examined for the detection of V. parahaemolyticus. A total of 120 presumptive vibrios wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Most strains of V. parahaemolyticus isolated from the environment or seafood, in contrast to clinical strains, do not produce tdh and trh (Alam et al, 2002;Ceccarelli et al, 2013;Shaw et al, 2014). In this study, the plasmid profiles did not correlate with antibiotic resistance patterns and our observation in agreement with similar findings reported by Silvester et al (2015).…”
Section: Discussionsupporting
confidence: 91%
“…Most strains of V. parahaemolyticus isolated from the environment or seafood, in contrast to clinical strains, do not produce tdh and trh (Alam et al, 2002;Ceccarelli et al, 2013;Shaw et al, 2014). In this study, the plasmid profiles did not correlate with antibiotic resistance patterns and our observation in agreement with similar findings reported by Silvester et al (2015).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of tdh + or trh + strains in seafood and environment is reported to be less and constitutes 1-10% of the isolates, whereas most of the clinical V. parahaemolyticus isolates carry tdh and/or trh genes (Cook et al, 2002;Deepanjali et al, 2005;Fuenzalida et al, 2006;Letchumanan et al, 2015Letchumanan et al, , 2014. Although there have been reports on the detection of tdh and trh gene from Cochin estuary and tiger shrimp culture environment in Cochin along the south-west coast, there are no major reports of detection of pathogenic V. parahaemolyticus carrying tdh and trh virulence genes from seafood (Chakraborty and Surendran, 2009;Silvester et al, 2015). In India, isolation of pathogenic isolates of V. parahaemolyticus possessing tdh gene from retail seafood is rarely reported (Dileep et al, 2003;Pal and Das, 2010;Parthasarathy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…1, 2) as observed in morphological, physiological and biochemical characterisation (Ananda Raja et al, 2017b). Similarly, Silvester et al (2015) confirmed 75 isolates as V P using a PCR assay targeting the species-specific tlh gene and found that the prevalence of V P was 71.6% in the Cochin Estuary and 53.3% in the shrimp farms. Letchumanan et al (2015a, b) indicated that a total of 57.8 and 44.4% isolates were positive for V P with toxR-based PCR assay.…”
mentioning
confidence: 54%